2022
DOI: 10.1177/10547738211069436
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Affecting Diet-Related Quality of Life Among Hemodialysis Patients According to Age-group

Abstract: This study identified factors influencing diet-related quality of life (QoL) among hemodialysis patients by age. In a cross-sectional correlational study in South Korea, 175 participants from two age groups—20–59 years and 60 years and above—completed self-report questionnaires assessing demographic and health-related characteristics, eating status, subjective health status, disease-related factors, dietary knowledge, and xerostomia severity. Findings indicated that the predictors of diet-related QoL included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(43 reference statements)
0
4
1
1
Order By: Relevance
“…It has long been known that diet and nutrition are crucial to relieve systemic inflammation ( 29 ) and muscle wasting ( 30 ), improve quality of life ( 31 ), and decrease mortality risk in patients undergoing hemodialysis. A thorough understanding of diet in patients is a fundamental element in designing or conducting nutritional interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that diet and nutrition are crucial to relieve systemic inflammation ( 29 ) and muscle wasting ( 30 ), improve quality of life ( 31 ), and decrease mortality risk in patients undergoing hemodialysis. A thorough understanding of diet in patients is a fundamental element in designing or conducting nutritional interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the self-e cacy score was not related to physical parameters, even when the relationship was analyzed separately in young and elderly patients (Additional le 5). It is likely that we should analyze the importance of the self-e cacy questionnaire using more patients according to age group [27]. In addition, our study showed that patients without employment and those with lower GNRI had signi cantly higher self-e cacy scores.…”
Section: Discussionmentioning
confidence: 74%
“…This may be because these patients have become accustomed to and adjusted to their lifeprolonging condition, whereas patients receiving relatively short-term dialysis had better mental health [15]. It was discovered that the following factors contributed to the lower quality of life of dialysis patients with chronic renal Journal Pharmaceutical and Medical disease: age and length of hemodialysis [16].…”
Section: Relation Between Duration Of Dialysis Age Materials Status A...mentioning
confidence: 99%